Risks from solar-powered groundwater irrigation: Emissions reductions may not meet expectations, and groundwater use will likely increase - Balasubramanya, Soumya; Garrick, Dustin; Brozović, Nicholas; Ringler, Claudia; Zaveri, Esha; Rodella, Aude-Sophie; Buisson, Marie-Charlotte; Schmitter, Petra S.; Durga, Neha; Kishore, Avinash; Minh, Thai Thi; Kafle, Kashi; et al. (American Association for the Advancement of Science, 2024)
Emissions reductions may not meet expectations, and groundwater use will likely increase